The Paradox of Pedestrian Comfort and Service Quality in a Tourism Corridor : A Case Study of Jalan Danau Tamblingan, Sanur - Agusintadewi, Ni Ketut (EMARA: Indonesian Journal of Architecture, 2025)
Pedestrian facilities are components of urban and tourism infrastructure to ensure access, safety, and comfort for users. On the pedestrian path along Jalan Danau Tamblingan, Sanur—a tourism corridor major route—issues have undermined the user experience. This study aims to investigate the level of pedestrian comfort and service quality within the area. The methodology employed was mixed-methods, combining qualitative observation and interviews to assess environmental and spatial conditions with quantitative analysis of pedestrian density, walking speed, and pedestrian flow through Level of Service (LOS) measurements. The results reveal a paradox: while the pedestrian path was given an LOS A rating, indicating free flow and low conflict, the comfort assessment rate was only 2 out of 8 satisfied criteria. One of the core deficiencies was circulation clarity, cleanliness, aesthetics, and odor control, although climate and safety demands were adequately met. The analogy here is to highlight pedestrian quality cannot be assessed by traffic efficiency but must also cater to environmental and experiential ones. The study concludes Jalan Danau Tamblingan allows for pedestrian efficiency but does not contribute to a pleasant walking environment for its residents and visitors. Closing these gaps requires in-depth design, upkeep, and administration improvements to enhance both functional and experience qualities. These are significant not only in local tourism mobility but also in creating urban livability and economic resilience in Sanur